Prevalence of extraintestinal manifestations and other associated conditions in a cohort of patients with inflammatory bowel disease at an advanced specialty center in Bogotá, Colombia - J. Andrade-Restrepo; D. Rubio-Cruz; J.G. Maigual-Quintas; S.G. Sicard-Gómez; E.J. Cuello-Navarro; L.C. Álvarez-Larrota; R. García-Duperly; E.E. Londoño-Schimmer; A.M. Rey-Rubiano; B. Mendoza de Molano; R.P. López-Panqueva (Revista de Gastroenterología de México (English Edition))
Introduction and aims: The prevalence and incidence of inflammatory bowel disease (IBD) has increased significantly in Latin America. Extraintestinal manifestations (EIMs) have elevated morbidity and are poorly characterized in the region. Our aim was to describe the characteristics of EIMs in patients with IBD at the Hospital Universitario Fundación Santa Fe de Bogotá, utilizing the EIM classification proposed by the European Crohn’s and Colitis Organisation (ECCO). Materials and methods: A cross-sectional study was conducted based on an institutional database of patients with IBD and the EIM definition used by the ECCO. Prevalence and prevalence ratios (PRs) of the EIMs were calculated. Results: The study included 168 patients, 66 of whom were diagnosed with Crohn’s disease (CD) and 102 with ulcerative colitis (UC). A total of 30.4% patients had at least one EIM, and the most frequent were oral ulcers (13.7%), arthritis (10.1%), and uveitis/episcleritis (6.5%). There was a greater prevalence of EIMs in CD (31.8% vs 29.40% in UC) and women (32.47% vs 28.57% in men). There was a significant PR between uveitis/episcleritis and arthritis, erythema nodosum and arthritis, and erythema nodosum and other eye diseases. Conclusions: Our study shows a high prevalence of EIMs, surpassing that of previous Colombian studies, with a predominance of CD. Oral manifestations stand out as the most common. Prevalence studies on EIMs in Colombia are needed to establish multidisciplinary specialized centers, improving the quality of life of patients with IBD. Resumen: Introducción y objetivos: La prevalencia e incidencia de la Enfermedad Inflamatoria Intestinal (EII) ha aumentado significativamente en América Latina. Las Manifestaciones Extraintestinales (MEI), tienen morbilidad elevada y están poco caracterizadas en la región. El objetivo de este estudio es describir las características de las manifestaciones extraintestinales en pacientes con EII del Hospital Universitario Fundación Santa Fe de Bogotá, utilizando la clasificación de MEI propuesta por la Organización Europea de Enfermedad de Crohn y Colitis (ECCO). Materiales y métodos: Se realizó un estudio transversal a partir de una base de datos institucional de pacientes con EII y la definición de MEI por la Organización Europea de Enfermedad de Crohn y Colitis (ECCO). Se calcularon la prevalencia y las razones de prevalencia (RP) entre las MEI. Resultados: Se incluyeron 168 pacientes, 66 diagnosticados con Enfermedad de Crohn (EC) y 102 con Colitis Ulcerosa (CU). El 30.4% presentaba al menos una MEI. Las más comunes fueron úlceras orales (13.7%), artritis (10.1%) y uveítis / epiescleritis (6.5%). Se observó una mayor prevalencia de MEI en EC (31.8% vs. 29.40% en CU) y en mujeres (32.47% vs. 28.57% en hombres). Se encontró una RP significativa entre uveítis/epiescleritis y artritis, eritema nodoso y artritis, y eritema nodoso y enfermedades oculares. Conclusiones: Este estudio muestra una alta prevalencia de MEI, superando investigaciones previas en Colombia, con una predominancia en EC. Las manifestaciones orales destacan como las más comunes. Se necesitan estudios de prevalencia sobre MEI en Colombia para establecer centros especializados multidisciplinarios que mejoren la calidad de vida de los pacientes con EII.